(untitled) (Acta Scientiarum. Health Sciences, 2020)
The natural history of cervical cancer is strongly related to the presence of human papillomavirus (HPV) infection, with its relationship with cervical cancer being a matter of concern. It is estimated that 70% of all cervical cancers worldwide are caused by HPV 16 and 18. Accordingly, the present study aimed to contribute to the identification of HPV subtypes circulating in a group of women of Manaus-Brazil. Cervical samples were collected from 49 women, following the eligibility criteria of the study, and DNA was then extracted from the samples, which were analyzed for the presence of the virus in the genetic material through the polymerase chain reaction (PCR) using generic primers (GP05/06). Finally, identification of the viral subtypes was performed using specific primers for the detection of the main subtypes already examined (16 and 18). Positive HPV DNA was detected in 100% of the samples included in the study. Human papillomavirus 16 was the most prevalent subtype in the majority of lesions, accounting for 29 (59.2%) of the positive cases, and HPV 18 was detected in four (8.2%) women. In these 4 cases there was co-infection, with the presence of both HPV 18 and HPV 16. Therefore, 40.8% (20 cases) in which HPV DNA was detected presented infection with other subtypes of HPV not included in the study. This data has clinical implications related to cervical cancer prevention, as the current prophylactic HPV vaccines are only effective against high-risk HPV 16 and 18 subtypes.